Матрична модель 4R & WS для класифікації стейкхолдерів проекту - Гусєва, Юлія Юріївна; Мартиненко, Олександр Сергійович; Чумаченко, Ігор Володимирович (НТУ "ХПІ", 2017)
Пропонується модель класифікації стейкхолдерів проекту, яка встановлює зв’язки між окремими характеристиками проекту (ризики, роботи, ресурси, вимоги, стейкхолдери та відповідальні особи проекту – 4R & WS) за допомогою ієрархічної структури робіт. Представлено концептуальну модель ідентифікації стейкхолдерів проекту у вигляді кубу 4R & WS. Запропонована модель дозволяє відстежувати динаміку виконання проекту та ідентифікувати зацікавлені сторони проекту за напрямами моделі 4R & WS.

A model for the classification of project stakeholders, which establishes interrelation between the individual characteristics of the project (risks, works, resources, requirements, stakeholders and responsible persons of the project – 4R & WS) using a Work Breakdown Structure is proposed. A conceptual model of stakeholders identification in the form of the 4R & WS cube is proposed. The proposed model makes it possible to monitor the dynamics of the project and identify the stakeholders of the project in directions of the 4R & WS model. A classification of project stakeholders will provide information on the resource and risk load of specific stakeholder’s requirements that will enable more considered planning of engagement strategy of stakeholders and management of project stakeholders’ requirements.
Matrix Model 4R & WS for the classification of the project stakeholders
Keywords: зацікавлені сторони; стейкхолдери; ідентифікація; класифікація; проект; interested parties; stakeholders; identification; classification; project